2012
DOI: 10.1016/j.gene.2012.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen regulates iron homeostasis through governing hepatic hepcidin expression via an estrogen response element

Abstract: a b s t r a c t a r t i c l e i n f oIron is essential for the human being, involving in oxygen transport, energy metabolism and DNA synthesis. Iron homeostasis is tightly governed by the hepcidin-ferroportin axis, of which hepcidin is the master regulator. Excess iron is associated with various diseases including osteopenia and osteoporosis, which are closely related to the alternation of the endogenous estrogen level. To verify the biological effect of estrogen on iron metabolism, we established a mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
167
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 44 publications
10
167
2
Order By: Relevance
“…As shown in Fig. 7B, the transcriptional activity of Pro-ERE was reduced by 20% upon E2 treatment, whereas the response to E2 was thoroughly lost in Pro-EREΔ transfected cells, similar to the mechanism of E2-mediated repression of hepcidin, in our previous study [23]. These findings therefore suggested that the putative ERE (−376/−388 bp) functionally responded to E2.…”
Section: Fpn Transcription Was Regulated By E2 Through a Functional Esupporting
confidence: 83%
See 4 more Smart Citations
“…As shown in Fig. 7B, the transcriptional activity of Pro-ERE was reduced by 20% upon E2 treatment, whereas the response to E2 was thoroughly lost in Pro-EREΔ transfected cells, similar to the mechanism of E2-mediated repression of hepcidin, in our previous study [23]. These findings therefore suggested that the putative ERE (−376/−388 bp) functionally responded to E2.…”
Section: Fpn Transcription Was Regulated By E2 Through a Functional Esupporting
confidence: 83%
“…Hou and colleagues from our research group previously identified an ERE within the promoter of hepcidin, and this ERE was responsible for E2-induced suppression of hepcidin expression in hepatocytes [23]. Therefore, we assumed that the promoter of FPN might also harbor a similar estrogen response site.…”
Section: Fpn Transcription Was Regulated By E2 Through a Functional Ementioning
confidence: 96%
See 3 more Smart Citations